2015
DOI: 10.1242/jcs.169383
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde transport is not required for cytosolic translocation of the B-subunit of Shiga toxin

Abstract: Antigen-presenting cells have the remarkable capacity to transfer exogenous antigens to the cytosol for processing by proteasomes and subsequent presentation on major histocompatibility complex class-I (MHC-I) molecules, a process termed cross-presentation. This is the target of biomedical approaches that aim to trigger a therapeutic immune response. The receptor-binding B-subunit of Shiga toxin (STxB) has been developed as an antigen delivery tool for such immunotherapy applications. In this study, we have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…Also, the choice of their targets and the way they modify them is amazingly optimised and, therefore, every new mode of action of a bacterial toxin has also brought novel findings about cellular function and homeostasis. For example, what will we learn when we understand how toxins without a pore-forming domain make it from the endosome to cytosol (Alami, Taupiac, Reggio, Bienvenüe, & Beaumelle, 1998;Beaumelle, Alami, & Hopkins, 1993;Garcia-Castillo et al, 2015)? What is the relevance of multiple phenotypes targeted by pore-forming toxins, namely, how do pore-forming toxins lead to the fission or vacuolation of the ER (Brito, Cabanes, Sarmento Mesquita, & Sousa, 2019;Gonzalez et al, 2018;Mesquita et al, 2017)?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Also, the choice of their targets and the way they modify them is amazingly optimised and, therefore, every new mode of action of a bacterial toxin has also brought novel findings about cellular function and homeostasis. For example, what will we learn when we understand how toxins without a pore-forming domain make it from the endosome to cytosol (Alami, Taupiac, Reggio, Bienvenüe, & Beaumelle, 1998;Beaumelle, Alami, & Hopkins, 1993;Garcia-Castillo et al, 2015)? What is the relevance of multiple phenotypes targeted by pore-forming toxins, namely, how do pore-forming toxins lead to the fission or vacuolation of the ER (Brito, Cabanes, Sarmento Mesquita, & Sousa, 2019;Gonzalez et al, 2018;Mesquita et al, 2017)?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…As an example, TAT-conjugated proteins are efficiently taken up by various cell lines, but only in the case of dendritic cell a cytosolic distribution of the endocytosed carriers could be observed [ 161 ]. Similarly, it was also demonstrated that endosomal escape of a lectin–saporin conjugate was more efficient in APCs than in cancer cell lines [ 162 ]. The reasons underlying efficient endosomal escape in APCs are still not understood at this stage.…”
Section: Endosomal Escapementioning
confidence: 99%
“…Certain toxins exert their cytotoxic activity specifically in the cytosolic compartment. For instance, pseudomonas exotoxin [ 173 , 174 ], alpha-sarcin, and saporin [ 140 , 162 ], once in the cytosol, lead to protein biosynthesis inhibition. Combinations of these toxins with vectors or endosomolytic agents have been used to monitor arrival in the cytosol.…”
Section: Endosomal Escapementioning
confidence: 99%
“…Both wildtype VT and CT were also able to rescue F508delCFTR, despite potent protein synthesis inhibition by VT. B subunits of CT were not effective. The inactivated holotoxoids showed a dose dependent rescue of F508delCFTR, though the optimal dose varied for different cell lines, likely due to the relative toxin cell line sensitivity, which depends on many factors, including glycolipid receptor expression [80,81], its ceramide structure[82,83] and membrane organization [84,85, 86], A bell-shaped response may be due to additional B subunit signaling responses[87,88]. A dose of 100ng/mL (1.3nM) was generally effective.…”
Section: Discussionmentioning
confidence: 99%